The Aspect of Assurance of Digital Institutional Repository Service Provision to Postgraduates Students at Selected Universities in Meru County - Mjeni, Sophia Tsenga; Gichohi, Paul Maku; Gichoya, David (International Journal of Professional Practice, 2023)
Theses, dissertations, reports and other research works by university communities are housed in digital institutional repositories in the library department. Postgraduate students are expected to utilize these resources; hence, the nature of services provided therein is critical. The provision of digital institutional repository service in university libraries is expected to be courteous, professional, and credible. Professionalism is demonstrated through politeness, trustworthiness, honesty, friendliness, respectfulness and competence of the institutional repository staff serving users. These attributes usually communicate assurance and heighten customer satisfaction. The feeling of assurance is also reinforced by the experience that a user gets when interacting with the repository website; for example, the friendliness of the webpages. However, incidences of users getting disinterested and losing patience with institutional repositories have continued to be reported.This paper reports part of findings of a large study which aimed to determine how adopting SERVQUAL model can improve digital institutional repository information services to postgraduate students at universities in Meru County. This paper assessed the assurance of digital institutional repository service provision. It employed a descriptive survey research design. The target population constituted library head of sections and post-graduate students. Purposive sampling was employed to get librarians, while simple random sampling, to select students. A sample size of 101 was adopted. Data was collected using questionnaires and interviews. Data quality was achieved by checking construct, content and face validity, while reliability was ascertained using Cronbach alpha. Data was analysed descriptively and thematically. The study found that the level of assurance in digital institutional repositories at universities in Meru County was moderate. Assurance aspects are supported by elements like: knowledgeable staff, customer-centric service, adequate ICT infrastructure, resources and facilities; customer awareness; and adequate funding. The study recommended creation of awareness, staff training and upgrading the repository technology to enhance assurance aspects.